Cultura e política: a natureza da guerra moderna no pensamento de Carl von Clausewitz - Lemos, Thiago Tremonte de (2008)
The purpose of this thesis is to argue the nature of the war in the thought of Carl von Clausewitz, from its workmanship On war. From modernity, the politics started to walk, through the national State, articulated to the war as one continuum. The military experiences lived by Clausewitz, at the end of century 18th and the beginning of century 19th, had been the source of its reflection, to the step that the aristocratic tradition offered a controversy and singular prism to observe the new Europe that appeared: bourgeois and nationalistic. Between The decay of the privileges of its class and the constitution of a new structure politics, Clausewitz said what it is the modern war. Its critics attribute to its thought the cause of many conflicts of century 20th. The modern concept of the war multiplies, runs away to its social context, and reproduces in other ideas and action